Conformational changes in a photosensory LOV domain monitored by time-resolved NMR spectroscopy. - Harper, S; Neil, L; Day, I; Hore, P; Gardner, K (2004)
Phototropins are light-activated kinases from plants that utilize light-oxygen-voltage (LOV) domains as blue light photosensors. Illumination of these domains leads to the formation of a covalent linkage between the protein and an internally bound flavin chromophore, destabilizing the surrounding protein and displacing an alpha-helix from its surface. Here we use a combination of spectroscopic tools to monitor the kinetic processes that spontaneously occur in the dark as the protein returns to the noncovalent ground state. Using time-resolved two-dimensional (2D) NMR methods, we measured the rate of this process at over 100 independent sites throughout the protein, establishing that regeneration of the dark state occurs cooperatively within a 1.6-fold range of observed rates. These data agree with other spectroscopic measurements of the kinetics of protein/FMN bond cleavage and global conformational changes, consistent with these processes experiencing a common rate-limiting step. Arrhenius analyses of the temperature dependence of these rates suggest that the transition state visited during this regeneration has higher energy than the denatured form of this protein domain despite the fact that there is no global unfolding of the domain during this process.